Nilai Pendidikan Karakter dalam Novel Malaikat-malaikat Penolong Karya Abdulkarim Khiaratullah - Meisusri, Silvi; Asri, Yasnur; Nst., M. Ismail (Universitas Negeri Padang, 2012)
This research have purpose to describe and analyze the value of character education that contained in Malaikat-malaikat penolong’s novel by Abdullah Khiaratullah, which consist of : (1) the value of honest, (2) tolerance, (3) hard work, (4) creative, (5) curiosity, (6) friendly/ communicative, (7) love peace, (8) social care,and (9) responsibility. The method that used for collecting the data are reading and understanding the novel carefully. After that, take note and mark the parts of story that indicates the value of character education. The method that used in analyzing the data are (1) inventory the value of education into the data research, (2) clasify according to the problems that researched, (3) analyze the data, (4) making the conclusion, and (5) make the report of findings.